Addiction [soundrecording] the sacred disease - Peck, M. Scott 1936- (Further along the road less traveled, 1991)
Explores the misguided tendency of individuals to substitute an addiction for a true relationship to God. Citing the community-building thombs of recovery groups, Dr. Peck demonstrates how the spiritual potential of the addictive personality can be harnessed productively instead of destructively.